Molecular identity of axonal sodium channels in human cortical pyramidal cells - Tian, Cuiping; Wang, Kaiyan; Ke, Wei; Guo, Hui; Shu, Yousheng (Frontiers in Cellular Neuroscience, 2014)
Studies in rodents revealed that selective accumulation of Na+ channel subtypes at the axon initial segment (AIS) determines action potential (AP) initiation and backpropagation in cortical pyramidal cells (PCs); however, in human cortex, the molecular identity of Na+ channels distributed at PC axons, including the AIS and the nodes of Ranvier, remains unclear. We performed immunostaining experiments in human cortical tissues removed surgically to cure brain diseases. We found strong immunosignals of Na+ channels and two channel subtypes, NaV1.2 and NaV1.6, at the AIS of human cortical PCs. Although both channel subtypes were expressed along the entire AIS, the peak immunosignals of NaV1.2 and NaV1.6 were found at proximal and distal AIS regions, respectively. Surprisingly, in addition to the presence of NaV1.6 at the nodes of Ranvier, NaV1.2 was also found in a subpopulation of nodes in the adult human cortex, different from the absence of NaV1.2 in myelinated axons in rodents. NaV1.1 immunosignals were not detected at either the AIS or the nodes of Ranvier of PCs; however, they were expressed at interneuron axons with different distribution patterns. Further experiments revealed that parvalbumin-positive GABAergic axon cartridges selectively innervated distal AIS regions with relatively high immunosignals of NaV1.6 but not the proximal NaV1.2-enriched compartments, suggesting an important role of axo-axonic cells in regulating AP initiation in human PCs. Together, our results show that both NaV1.2 and NaV1.6 (but not NaV1.1) channel subtypes are expressed at the AIS and the nodes of Ranvier in adult human cortical PCs, suggesting that these channel subtypes control neuronal excitability and signal conduction in PC axons.